Need for speed: bacterial effector XopJ2 is associated with increased dispersal velocity of Xanthomonas perforans. (8th June 2021) - Sharma, Anuj; Timilsina, Sujan; Abrahamian, Peter; Minsavage, Gerald V.; Colee, James; Ojiambo, Peter S.; Goss, Erica M.; Vallad, Gary E.; Jones, Jeffrey B.
Summary: Bacterial spot caused by Xanthomonas perforans ( Xp ) is an economically important disease in tomato. Previous studies have shown that the recently isolated Xp strains have acquired and retained the effector gene, xopJ2, which has been reported to increase fitness of the pathogen in the field. To elucidate the fitness benefit of xopJ2, we quantified the effect of xopJ2 on the dispersal and evolution of Xp populations on tomato. We compared movement of two wild‐type Xp strains expressing xopJ2 to their respective xopJ2 mutants when co‐inoculated in the field. We developed a binary logistic model to predict the presence of Xp over spatial and temporal dimensions with or without xopJ2 . Based on the model, wild‐type bacteria were dispersed approximately three times faster than the xopJ2 mutants. In a simulation experiment, the selective advantage due to increased dispersal velocity led to an increase in the frequency of xopJ2 gene in the Xp population and its apparent fixation within 10 to 12 cropping seasons of the tomato crop. Our results show that the presence of a single gene can affect the dispersal of a bacterial pathogen and significantly alter its population dynamics.